2021
DOI: 10.1016/j.jseint.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on shoulder and elbow trauma in a skeletally immature population: an Italian survey

Abstract: Background Aim of this study was to evaluate the impact of COVID-19 on the shoulder and elbow trauma in a skeletally immature population in 30 days starting from the March 8 2020, the first day of restrictions in Italy, and to compare it with the same days of 2019. Materials and methods All the skeletally immature (younger than 18 ys) patients managed in the Emergency Unit of our Hospital between March 8 2020 and 8 th April 2020 (COVID-19 peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
1
18
0
2
Order By: Relevance
“…There was a worldwide reduction of between 20.3% and 84.6% in trauma patients compared to a pre-COVID control period. 10 , 11 , 12 , 13 , 14 , 15 , 17 , 19 , 20 , 25 , 27 , 34 , 35 , 37 , 41 , 42 , 43 , 44 , 45 , 46 Hernigou et al 16 reported a concomitant increase in paediatric trauma and reduction in adult trauma during the pandemic at their centre in Belgium, a finding replicated in one Australian centre. 47 Additionally, Wong et al‘s centre based in Australia reported no change in paediatric trauma requiring acute admission.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…There was a worldwide reduction of between 20.3% and 84.6% in trauma patients compared to a pre-COVID control period. 10 , 11 , 12 , 13 , 14 , 15 , 17 , 19 , 20 , 25 , 27 , 34 , 35 , 37 , 41 , 42 , 43 , 44 , 45 , 46 Hernigou et al 16 reported a concomitant increase in paediatric trauma and reduction in adult trauma during the pandemic at their centre in Belgium, a finding replicated in one Australian centre. 47 Additionally, Wong et al‘s centre based in Australia reported no change in paediatric trauma requiring acute admission.…”
Section: Resultsmentioning
confidence: 90%
“…The mean age was reported for 3236 patients and was 43.7 years. 13 , 18 , 19 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 An average of 54.8% were male.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of injuries was different during the lockdown period, as most traumas occurred at home (82%) compared with 2019, during which sports accidents were the most common cause of injury (34.7%). As most fractures occurred at home, targeted measures should be considered to prevent such injuries effectively [ 20 , 21 ]. The superior limb was the most involved segment for fractures both in the lockdown and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease could be especially prevalent given the typical increase in pediatric injury presentation in the spring and fall seasons when sport activities are most common. 11,21 Significant delays to care and decreased patient volume have been observed in a variety of medical subspecialties, including orthopaedic surgery, 4,10 as a result of the COVID-19 pandemic. 16,17,24 This may suggest reluctance for patients to seek medical care because of concerns for increased COVID-19 exposure.…”
mentioning
confidence: 99%